Dynamics and immunomodulation of cognitive deficits and behavioral changes in non-severe experimental malaria - Rosa-Gonçalves, Pamela; de Sousa, Luciana Pereira; Maia, Aline Barbosa; Ribeiro-Gomes, Flávia Lima; Gress, Caroline Cristhiani Tavares de Lima; Werneck, Guilherme Loureiro; Souza, Diogo Onofre; Almeida, Roberto Farina; Daniel-Ribeiro, Cláudio Tadeu (Frontiers in Immunology, 2022)
Data recently reported by our group indicate that stimulation with a pool of immunogens able to elicit type 2 immune responses can restore the cognitive and behavioral dysfunctions recorded after a single episode of non-severe Plasmodium berghei ANKA malaria. Here we explored the hypothesis that isolated immunization with one of the type 2 immune response-inducing immunogens, the human diphtheria-tetanus (dT) vaccine, may revert damages associated with malaria. To investigate this possibility, we studied the dynamics of cognitive deficits and anxiety-like phenotype after non-severe experimental malaria and comparatively evaluated the effects of dT immunization and of a pool of type 2 immune stimuli in reverting these impairments. Locomotor activity and long-term memory deficits were assessed through the open field test (OFT) and novel object recognition task (NORT) and the anxiety-like phenotype was evidenced by OFT and light/dark task (LDT). Our results indicate that poor performance in cognitive-behavioral tests is detected as early as at the 12th day after the end of antimalarial treatment with chloroquine and may persist for up to 155 days post infection. The single immunization strategy with the human dT vaccine revealed as promising to revert long-term memory deficits in NORT and anxiety-like behavior in OFT and LDT.